Numeracy and Environmental Awareness Attitudes of Primary School-Age Children in the Malind Community - Ni Nyoman Rediani; Trinovianto G. R Hallatu; Ivylentine Datu Palittin; Hanova Rani E. Retnaningtyas; Herrio Tekdi Nainggolan; Sunarni Sunarni; Yus Witdarko; Yusri Yusri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examines students' numeracy abilities and attitudes toward environmental awareness among primary school-age children. Through an in-depth understanding of these two aspects, this study aims to provide a strong foundation for formulating appropriate solutions and learning methods that align with the needs and conditions of primary school-age children. Methodology: This research employed a descriptive method with a quantitative approach to explore numeracy literacy capabilities and attitudes toward environmental awareness. The descriptive research design was structured to provide detailed descriptions of the conditions or characteristics of the phenomena under study, focusing on